PERBANDINGAN BUDAYA INDONESIA DAN JEPANG (TINJAUAN TRADISI PENAMAAN DAN GERAK ISYARAT TUBUH) - Novi Andari (Universitas 17 Agustus 1945 Surabaya, 2009)
Abstract. Knowing the thinking pattern of the Indonesian nation and that of the Japanese nation is useful in an effort to understand the different culture between Indonesian and Japanese. One of the main difficulties is the different characteristics of the two peoples: the Japanese people are relatively homogeneous, while the Indonesian people are very heterogeneous. Therefore, comparisons will be easier if it is focused on comparing Japanese culture and one ethnic group in Indonesia. For example, Japanese culture with the cultures of Central Java, or Japanese culture with the culture of Sunda. This leads us to the next questions that Â whether the Indonesian nation has a national culture, or that national culture is nothing but a collection of colorful ethnic culture of our nation. This is not an easy question to answer, and interesting to be further analyzed.Â Key words: definiton of names, signature meaning, gestures